2008
DOI: 10.1152/japplphysiol.90495.2008
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of iNOS attenuates trauma-hemorrhage/resuscitation-induced hepatic injury

Abstract: IH. Selective inhibition of iNOS attenuates trauma-hemorrhage/resuscitation-induced hepatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 44 publications
4
35
1
4
Order By: Relevance
“…Instead we measured nitrotyrosine, a downstream, validated surrogate of nitric oxide formation. 18,19 Nitrotyrosine (Northwest Life Science Specialties, LLC) was detected by enzyme-linked immunoadsorbent assay (ELISA). Cytokines were also measured by ELISA (R&D Systems).…”
Section: Study Protocolmentioning
confidence: 99%
“…Instead we measured nitrotyrosine, a downstream, validated surrogate of nitric oxide formation. 18,19 Nitrotyrosine (Northwest Life Science Specialties, LLC) was detected by enzyme-linked immunoadsorbent assay (ELISA). Cytokines were also measured by ELISA (R&D Systems).…”
Section: Study Protocolmentioning
confidence: 99%
“…Therefore, we used the highly selective iNOS inhibitor 1400W in our present study. It has been reported that 1400W inhibited iNOS activity by binding with iNOS [27] , but some studies found that 1400W could decrease iNOS expression [28,29] . In this study, we also found that iNOS expression was increased significantly in vascular tissue of aged rats.…”
mentioning
confidence: 99%
“…T he innate immune system has been shown to contribute to immune-mediated liver damage associated with hepatic ischemia/reperfusion (I/R) injury, hepatitis, hemorrhagic shock, and other inflammatory liver disease states (1)(2)(3)(4)(5)(6). NKT cells represent a unique group of T lymphocytes that are reactive to self and foreign glycolipid Ags presented by the MHC class Irelated molecule CD1d (7)(8)(9).…”
mentioning
confidence: 99%